The Role of Applying IAS and Iraqi Local Rules in Inventory Valuation and Their Impact on Tax Revenue: An Applied Study to A Sample of Iraqi Companies Listed in The Iraqi Stock Exchange - Gheni Jihad, Asaad; Abdullah Al Baaj, Qassim Mohammed; Hamzah albudairi, Asaad Hameed (Opción, 2019)
The problem of inventory valuation is one of the essential issues that raises scientific controversy among many accountants because of the multiplicity of local and international accounting standards through the valuation meth- ods emanating from them. This leads to different results and effects on the financial income statement and the balance sheet of the company, which affects the tax revenues due to them. Accounting organizations and profes- sional associations have confirmed that the inventory component has a sig- nificant and significant impact on the financial statements. The objective of the research is to examine the International Accounting Standard(IAS) No.2 ( the amended international standard) and the Iraqi Local Accounting Rule No. 5 related to the choice of inventory valuation methods and their impact on costing the value of the inventory at the end of the accounting period and its disclosure in the financial statements and comparing the effect of the methods used for evaluating the inventory according to the International and Local Accounting Standards and that effect on the tax revenues of the com- panies in a product of the companies of the industry sector. The statistical analysis of the article has been based on FIFO, LIFO, and WAC methods of inventory valuation.